Returning home during the pandemic: a thematic analysis describing experiences of people with substance use disorders released early from New Jersey prisons during COVID-19 - Madeline H. Bono; Peter Treitler; Brendan Saloner; Stephen Crystal (BMC, 2023)
Abstract Background & aims The COVID-19 pandemic created intersecting health risks for incarcerated people with a history of substance use disorder (SUD). To reduce exposure to COVID-19 in prison, several US states enacted decarceration legislation. New Jersey enacted the Public Health Emergency Credit Act (PHECA), granting early release to thousands of incarcerated persons meeting eligibility criteria. This study undertook to explore how large scale decarceration during the pandemic impacted the reentry process for released individuals with SUDs. Methods Twenty seven participants involved in PHECA releases - 21 persons released from NJ carceral facilities with past/present SUDs (14 with opioid use disorder, 7 with other SUDs) and 6 reentry service providers acting as key informants - completed phone interviews on PHECA experiences from February-June 2021. Cross-case thematic analysis of transcripts identified common themes and divergent perspectives. Results Respondents described challenges consistent with long-documented reentry difficulties including housing and food insecurity, difficulty accessing community services, insufficient employment opportunities, and limited access to transportation. Challenges that were pertinent to mass release during a pandemic included limited access to communication technology and community providers and community providers exceeding enrollment capacity. Despite reentry difficulties, respondents identified many areas where prisons and reentry service providers adapted to meet novel challenges presented by mass decarceration during the COVID-19 pandemic. Facilitators made available by prison and reentry provider staff included providing released persons with cell phones, transportation assistance at transit hubs, prescription support for medications for opioid use disorder, and pre-release assistance with ID and benefits through NJ's Joint Comprehensive Assessment Plan. Conclusions Formerly incarcerated people with SUDs experienced reentry challenges during PHECA releases similar to those that occur during ordinary circumstances. Despite barriers faced during typical releases and novel challenges unique to mass release during a pandemic, providers made adaptations to support released persons' successful reentry. Recommendations are made based on areas of need identified in interviews, including reentry service provision facilitating housing and food security, employment, medical services, technology fluency, and transportation. In anticipation of future large scale releases, providers will benefit from planning ahead and adapting to address temporary increases in resource demands.